Design of a rotating disk reactor to assess the colonization of biofilms by free-living amoebae under high shear rates. Issue 4 (21st April 2018) - Perrin, A.; Herbelin, P.; Jorand, F. P. A.; Skali-Lami, S.; Mathieu, L.
Abstract: The present study was aimed at designing and optimizing a rotating disk reactor simulating high hydrodynamic shear rates ( γ ), which are representative of cooling circuits. The characteristics of the hydrodynamic conditions in the reactor and the complex approach used to engineer it are described. A 60 l tank was filled with freshwater containing free-living amoebae (FLA) and bacteria. Adhesion of the bacteria and formation of a biofilm on the stainless steel coupons were observed. FLA were able to establish in these biofilms under γ as high as 85, 000 s −1 . Several physical mechanisms (convection, diffusion, sedimentation) could explain the accumulation of amoeboid cells on surfaces, but further research is required to fully understand and model the fine mechanisms governing such transport under γ similar to those encountered in the industrial environment. This technological advance may enable research into these topics.